Prefrontal cortical control of a brainstem social behavior circuit - Franklin, Tamara; Grinevich, Valéry (Nature neuroscience, 2017)
The prefrontal cortex plays a critical role in adjusting an organism's behavior to its environment. In particular, numerous studies have implicated the prefrontal cortex in the control of social behavior, but the neural circuits that mediate these effects remain unknown. Here we investigated behavioral adaptation to social defeat in mice and uncovered a critical contribution of neural projections from the medial prefrontal cortex to the dorsal periaqueductal grey, a brainstem area vital for defensive responses. Social defeat caused a weakening of functional connectivity between these two areas and selective inhibition of these projections mimicked the behavioral effects of social defeat. These findings define a specific neural projection by which the prefrontal cortex can control and adapt social behavior.
Gesehen am 29.10.2018
Author manuscript available in PMC 2017 September 01